Pola Komunikasi Antara Mahasiswa dan dosen dalam Pembelajaran Online Program Studi Ilmu Komunikasi di Universitas Islam Makassar - Andi Muhammad Nur; Nahdiana Nahdiana (Journal of Communication Sciences (JCoS), 2022)
Online learning uses several learning applications and social networks. The role of technology in online learning is needed so we must have good knowledge and skills in the use and management of technology both as students and lecturers. This study aims to determine: 1) How is the pattern of communication between students and lecturers in online learning in the Communication Studies Program at the Islamic University of Makassar? 2) What factors support and hinder online learning between students and lecturers in the teaching and learning process? The type of research used is qualitative research with data collection techniques through interviews and documentation. Data analysis techniques used are data reduction techniques, data presentation, and drawing conclusions. The results of the study explain that: 1) The dominant communication pattern occurs in online lectures conducted by communication science students, namely a secondary communication pattern in which the process of delivering messages by the communicator to the communicant by using tools or facilities as the second medium after using the symbol on the first media. Communicators use this second media because the target of communication is far away or many in number. In this secondary communication process, the longer it will be more effective and efficient because it is supported by increasingly sophisticated information technology. In online lectures, communication that occurs is supported by the development of information technology, namely the internet 2). The supporting factors for online learning between students and lecturers in the teaching and learning process are the technology and media used, while the inhibiting factor for the internet network is one of the obstacles faced by students in online learning.